An Exemplar Frontal Plane Visual Kinematic Stimulus Elicits Sex-Specific Learned Behavior: An Exploratory Report. Issue 3 (12th March 2022) - Hogg, Jennifer A.; Riehm, Christopher D.; Diekfuss, Jed A.; Simon, Janet E.; Acocello, Shellie N.; Liang, Yu; Wu, Dalei; Myer, Gregory D.; Wilkerson, Gary B.
Abstract: Hogg, JA, Riehm, CD, Diekfuss, JA, Simon, JE, Acocello, SN, Liang, Y, Wu, D, Myer, GD, and Wilkerson, GB. An exemplar frontal plane visual kinematic stimulus elicits sex-specific learned behavior: An exploratory report. J Strength Cond Res 36(3): 857–861, 2022—The purpose of this exploratory study was to determine if a visually delivered kinematic stimulus designed to promote injury-resistant biomechanics would induce sex-specific motor learning effects. Six female subjects and 6 male subjects participated in 2 consecutive day sessions in which they mimicked an avatar performing 5 sets of 8 repetitions of exemplar frontal plane mechanics during single-leg squats. Acute (∼10 minutes) and delayed (∼24 hours) transfer testing under single-task (single-leg balance) and dual-task conditions (single-leg balance plus cognitive task) were referenced to baseline measurements. Center of pressure (CoP) mean velocity (Vel), SD, and detrended fluctuation analysis (DFA) in the anterior posterior (AP) and medial-lateral (ML) directions were quantified, with dual-task costs defined as the percentage difference from single-task to dual-task. Separate 2 × 3 repeated-measures analysis of variance was conducted for each dual-task cost variable. Main effects and interactions with large effect sizes considered as η p 2 ≥ 0.14 were further explored with pairwise post hoc comparisons. Sex by time interactions were observed for medial-lateral standard deviation cost (η p 2 = 0.29; p = 0.04), anterior-posterior standard deviation cost (η p 2 = 0.27; p = 0.06), and AP DFA cost (η p 2 = 0.41; p = 0.007), in which female subjects displayed lower dual task cost at acute transfer testing compared with male subjects (Cohen's d = 1.52, 1.64, 0.97; p = 0.03, 0.02, and 0.13 respectively). This report provides preliminary evidence that female subjects may be more responsive than male subjects to a prescribed frontal plane kinematic visual stimulus. Based on these sex-specific effects, future visually driven stimuli may require alternative strategies to optimize efficacy in male subjects.